Pengaruh Motif Berprestasi dan Self Efficacy Terhadap Pencapaian Target Penjualan Distributor - Yanti, Ayu Agustina Indra; Tripalupi, Lulup Endah; Haris, Iyus Akhmad (Universitas Pendidikan Ganesha, 2020)
This research aims to determine the effect of achievement motives and self efficacy on the achievement of sales targets for Tiens Bali distributors partially and simultaneously. This research design using a type of causal research. The population of this study were all distributors registered at Tiens Authorized Store 618 are 4.169 people. The sample of this study amounted to 371 respondents using the proportional random sampling method. The data collection technique was carried out by distributing questionnaires with a Likert scale and processed using multiple linear regression analysis technique. The result of data analysis showed that there was a partially positive and significant effect on the achievemnt motive towards achieving the sale target of Tiens Bali distributors, shown from the value of t=13.491 with a Sig. of 0.000 less than 0.05. Self efficacy, partially has a positive and significant effect on achieving the sales target of Tiens Bali distributors, shown from the value of t=12.915 with a Sig. of 0.000 less than 0.05. Achievement motives and self efficacy have a simultaneous positive effect on achieving sales targets of Tiens Bali distributors, shown by the value of F=323.925 and a Sig. of 0.000 less than 0.05.